Family Empowerment in Hypertension Control Through Slow Stroke Back Massage Training in Dusun II, Sidodadi Village - manik, maria hermita (INSTITUT KESEHATAN DELI HUSADA, 2026)
One of the most common non-communicable disorders is hypertension, which increases the risk of cardiovascular problems if left untreated. Pharmacological therapy is not the sole way to manage hypertension; non-pharmacological measures that are simple to implement in the community can also help, Slow-stroke back massage is one of them. The goal of this community service program is to increase families' understanding and proficiency with blood pressure management among hypertensive patients through training in slow stroke back massage at the Deli Tua Community Health Center.The implementation methods included health education, demonstrations, and direct training for families of hypertensive patients, as well as assistance in practicing slow stroke back massage. Evaluation was carried out by taking blood pressure readings both before and after the intervention and assessing improvements in participants' knowledge and skills. This activity involved families as primary caregivers in managing hypertensive patients at home.The results showed an increase in family knowledge and skills in performing slow stroke back massage, along with a tendency for decreased blood pressure among hypertensive patients after the intervention. Therefore, family empowerment through slow stroke back massage training can be a useful approach in supporting independent hypertension management in the community. It is anticipated that this program will function as a long-lasting community-based nursing intervention and enhance the active role of families in maintaining the health of their family members.